Long-Term Anatomical and Functional Survival of Boston Type 1 Keratoprosthesis in Congenital Aniridia - Dyer, Ariann; De Faria, Alix; Julio, Gemma; Álvarez de Toledo, Juan; Barraquer, Rafael I.; de la Paz, Maria Fideliz (Frontiers in Medicine, 2021)
Purpose: To analyze the long-term anatomical survival, functional survival, and complications of Boston type 1 keratoprosthesis (KPro) in the eyes with congenital aniridia-associated keratopathy (AAK). Methods: A retrospective review of 12 eyes with congenital aniridia that underwent a Boston type 1 KPro surgery was conducted. A Kaplan–Meier analysis was performed. Anatomical and functional success criteria were KPro retention and a best corrected visual acuity (BCVA) ≤1.3 LogMAR (≥0.05 decimal) at the end of a follow-up period. Postoperative complications were recorded. Results: The mean preoperative BCVA was 2.1 ± 0.9 (range: 3.8–1) LogMAR, and glaucoma was a comorbidity in all the cases. Five years after the surgery, the overall retention rate was 10/12 (83.3%), and 50% had functional success. Only three (25%) of the 12 cases did not achieve a BCVA ≤1.3 LogMAR. The cumulative probability of anatomical success was 92, 79, and 79% after 1, 5, and 10 years, respectively. The cumulative probability of functional success was 57 and 46% after 1 and 5 years, respectively. The mean anatomical and functional survival time was 10 ± 1.3 (95% IC = 7.5–12.3 years) and 3.8 ± 0.9 years (95% IC = 1.8–5.8 years), respectively. The most common postoperative complication was retroprosthetic membrane (RPM) formation in 8/16 cases (66%). The mean number of complications per case was 2.4 ± 1.8 (0–6). Conclusions: The Boston type 1 KPro is a viable option for patients with AAK with good anatomical and functional long-term results. Glaucoma is an important preoperative condition that affects functional results. Retroprosthetic membrane formation seems to have a higher incidence in this condition.